"The pluses of pulses": haricot beans and women's empowerment in Ethiopia. Issue 2 (17th February 2018) - Geleta, Esayas Bekele; Henry, Carol; Elabor-Idemudia, Patience
ABSTRACT: This practical note demonstrates the role that haricot beans play in assisting women to become food and nutrition secure, to generate income, and to have sustainable livelihoods that are resilient to shocks. Based on qualitative research among female and male beneficiaries of a pulse innovation project implemented in southern Ethiopia, the note provides a summary of the critical voices of farmers, and the role that haricot beans play in empowering women. It also outlines some of the challenges that the project faced in achieving its empowerment objectives.